Leveraging Peer Teaching for Global Health Elective Preparation: Implementation of a Resident-Led Global Health Simulation Curriculum - Fiona Pirrocco DO; Ian Goodman MD; Michael B. Pitt MD (SAGE Publishing, 2019)
Introduction . As more trainees engage in global health electives, the call for best practices in predeparture preparation grows. However, many residency programs may not have the infrastructure or staffing in place to consistently meet these expectations. Objective . To assess the feasibility, benefits, and limitations of having residents trained to facilitate and implement a global health preparatory simulation curriculum. Approach. In 2016, we had 5 residents undergo online Simulation Use for Global Away Rotations (SUGAR) facilitator training. Since then, we have conducted 3 simulation sessions from 2016 to 2018. Feedback was obtained from 75% of our participants, which was found to be similar to feedback obtained from attending-led models. Lessons Learned. A resident-led global health preparatory curriculum provides a sustainable model for residency programs without placing additional burden on attending faculty.